Synergistic effect of multiple molten salts on hot corrosion behaviour of Ni-based single crystal superalloy. (1st August 2022) - Yang, Y.Q.; Zhao, Y.C.; Wen, Z.X.; Lu, G.X.; Pei, H.Q.; Yue, Z.F.
Abstract: Hot corrosion behaviour of Ni-base single crystal at 900 ℃ is investigated under three different mixed salts. The result shows that hot corrosion degree in Na2 SO4 +NaCl+NaVO3 is the most serious, followed by Na2 SO4 + NaVO3, and Na2 SO4 +NaCl is the least. The hot corrosion mechanism of superalloy in Na2 SO4 +NaCl+NaVO3 salts is proposed. More importantly, the interaction of Na2 SO4, NaCl and NaVO3 is a synergistic relationship in which Na2 SO4 causes a basic corrosion attack, and NaCl with NaVO3 strengthen this attack. Therefore, in hot corrosion protection, the type of corrosive salt should be reduced to avoid the synergistic effect caused by multiple salts. Graphical Abstract: ga1 Highlights: Hot corrosion behavior of Ni-based single crystal superalloys at 900 ℃ under three different mixed salts was investigated. Sulfides in γ′-depleted layer are mainly affected by critical oxygen partial pressure and standard free energy of sulfide. NaCl and NaVO3 consume the protective oxides and prolong the time of internal sulfidation-oxidation cycle reaction. There is a synergistic relationship between the corrosion salts of Na2 SO4, NaCl and NaVO3 .